Validitas dan Praktikalitas Modul Kesetimbangan Ion dan pH Larutan Garam Berbasis Inkuiri Terbimbing - Sri Rahayu; Iryani Iryani (Edukimia, 2020)
This study aims to produce a module ion equilibrium and pH of salt solution and how to categorise module validity and practicality levels. As this is Research and Development study, we used Plomp model consisting three stages, preliminary research, prototyping stage and assessment phase. Guided inquiry is a learning model used in this study. This module is validated by 5 validators with a research instrument in validation and practicality sheet in the form of questionnaires. The validator’s evaluation of each statement was analysed using Kappa Cohen formula. The results show kappa moment value (κ) 0.85 with a very high category. The kappa moment value (κ) for practicality of module based on teacher’s response is 0.88, while student’s response is 0.81. The resulting module is very valid and practical to use.